Chapter Applications of the Selective Laser Melting Technology in the Industrial and Medical Fields - Ancuta, Pacurar (InTechOpen, 2016)
The existence of an MCP Realizer II SLM 250 equipment at the National Centre of Innovative Manufacturing from the Technical University of Cluj-Napoca (TUC-N) facilitated the starting of different research activities in this field at TUC-N with the aim of improving the Selective Laser Melting (SLM) process capability for a better transfer of the technological gained knowledge to different partners from the industrial and medical fields. Reaching this goal has been also facilitated by the fact that in the period 2010-2013 at the Technical University of Cluj-Napoca, within a postdoctoral project financed by European Commission (E.U.), it was possible to activate with the program entitled "Research regarding the manufacturing of metallic parts by Selective Laser Melting (SLM) technology." Part of the results obtained in this postdoctoral program are presented within this chapter of the book, being addressed not only to the engineers, PhD students, researchers, medical doctors, but also to anyone who might be interested about this Additive Manufacturing (AM) method and its possible applications in the industrial and medical fields.